Pengembangan Strategi Pemasaran Coffee Shop Salapan Djati - Agung Prabowo, Vetto; Patria, Vigar; Pertiwi Hari sandi, Santi; Epty Hidayaty, Dwi (Rifa'Institute, 2023)
This study aims to analyze and develop an effective marketing strategy system at the